Framing Terminology: A Process-Oriented Approach - Faber Benítez, Pamela; Márquez Linares, Carlos; Vega Expósito, Miguel (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2005)
AbstractThe frame notion used in Frame Semantics can be traced to case frames, which were said to characterize a small abstract situation in such a way that if one wished to understand the semantic structure of a verb it was necessary to understand the properties of the entire scene that it activated. A frame has been more broadly defined as any system of concepts related in such a way that one concept evokes the entire system. In this sense, it bears an obvious affinity with terminology, which is also based on such conceptual organization. However, despite the fact that Frame Semantics has been usefully applied to lexicology and syntax, so far it has not been systematically applied to terminology.This paper argues for a frame-based organization of specialized fields in which a dynamic process-oriented frame provides the conceptual underpinnings for the location of sub-hierarchies of concepts within a specialized domain event, and the elaboration of a definition template, thus opening the door to a more adequate representation of specialized fields as well as supplying a better way of linking terms to concepts. The domain of coastal engineering is used as an example because the entities in play take part in processes that are difficult to describe only by means of conceptual trees. Through the use of corpus data we demonstrate how it is possible to represent such an event and create a dynamic frame which enriches and enhances the understanding of specialized field concepts.